Isolation and identification of local white-rot fungi from West Sumatra and their potential for biodelignification of ruminant feed (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This research aimed to isolate and identify potential white-rot fungi from various locations in West Sumatra, Indonesia, that could be used for biodelignification of animal feed ingredients. Materials and Methods: Wood samples with fungal infections were directly observed, and the visual method was employed to collect samples. The purified white-rot fungi isolates underwent the Bavendamm test to evaluate their biodelignification capabilities. Results: Eight of the 15 purified white-rot fungi isolates demonstrated positive results in the Bavendamm test, indicating their potential for biodelignification. Further analysis revealed the presence of three indigenous white-rot fungi species in West Sumatra: Exidia sp., Trametes sp., and Phanerochaete sp. These findings highlight the richness of white-rot fungi biodiversity in the region and underscore their suitability for lignin degradation in animal feed ingredients. Additionally, the successful isolation and identification of these fungi represent a crucial step toward sustainable biotechnological applications in livestock farming. Conclusion: The identified white-rot fungi have shown promising capabilities for lignin degradation in animal feed ingredients. However, further research is essential to ascertain the optimal enzyme ratio for lignin degradation and to enhance the identification techniques for a broader range of white-rot fungi species. This study provides a foundational step toward improving animal feed quality in the region, especially for ruminants.J. Adv. Vet. Anim. Res., 12(2): 558–564, June 2025http://doi.org/10.5455/javar.2025.l920